Physics-informed neural networks for integrated traffic state and queue profile estimation: A differentiable programming approach on layered computational graphs - Lu, Jiawei; Li, Chongnan; Wu, Xin Bruce; Zhou, Xuesong Simon (Transportation research. Part C, Emerging technologies, 2023)
•Simultaneously perform traffic state estimation and queue profile estimation in an integrated framework.•Corridor-level system measure functions are analytically derived based on fluid queue model.•A novel continuous space–time approximation based traffic state representation scheme.•A reformulated nonlinear differentiable programming model solved on a computation graph. This paper presents an integrated framework for physics-informed joint traffic state and queue profile estimation (JSQE) on freeway corridors, utilizing heterogeneous data sources. The integrated modeling framework aims to maximize the benefits of information from physics-informed analytical traffic flow models and field observations while leveraging joint estimation spaces. Potential inconsistencies between different modeling components must be acknowledged and carefully managed to ensure model feasibility. To minimize such inconsistencies, a nonlinear programming model is formulated for the JSQE problem, taking into account traffic flow models and observations from both corridor and local segment levels. At the corridor level, a fluid queue approximation is employed to model queuing dynamics. Assuming polynomial arrival and departure rates, critical system variables such as time-dependent delay, travel time, and queue length are analytically derived. To preserve the differentiability of traffic state variables, continuous space–time distribution functions are introduced to model traffic flow variables and partial differential equations. A computational graph is constructed to represent the nonlinear programming model in a layered structure, which is then solved using a forward–backward method. Comprehensive numerical experiments based on real-world and hypothetical datasets are designed to demonstrate the effectiveness of the proposed framework.